1979
DOI: 10.1111/j.1365-2125.1979.tb04773.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamic studies of labetalol in hypertensive subjects.

Abstract: 1 The pharmacokinetics of labetalol were studied in twelve hypertensive patients, ten of whom were not receiving other therapy. 2 Following intravenous administration there was a three-to fourfold variation in terminal elimination half-life, volume of distribution and total plasma clearance. The mean elimination halflife was 3.25 hours. 3 Following oral administration the drug was absorbed rapidly. Systemic availability varied from 11-86% (mean 33%).4 Plasma levels correlated poorly with the acute effect on BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1981
1981
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 8 publications
1
16
1
Order By: Relevance
“…On the other hand plasma cyclic AMP increased after labetalol which may be explained by partial ,3-adrenoceptor agonist activity of the compound (Carey & Whalley, 1979;Riley, 1980) or by active metabolites of labetalol. The presence of such metabolites is also suggested by the poor correlation between plasma concentrations of labetalol and the hypotensive effect (McNeil et al, 1979) and perhaps by our chromatographic findings. As noted in the introduction labetalol may have haemodynamic advantages over e.g.…”
Section: Discussionsupporting
confidence: 52%
“…On the other hand plasma cyclic AMP increased after labetalol which may be explained by partial ,3-adrenoceptor agonist activity of the compound (Carey & Whalley, 1979;Riley, 1980) or by active metabolites of labetalol. The presence of such metabolites is also suggested by the poor correlation between plasma concentrations of labetalol and the hypotensive effect (McNeil et al, 1979) and perhaps by our chromatographic findings. As noted in the introduction labetalol may have haemodynamic advantages over e.g.…”
Section: Discussionsupporting
confidence: 52%
“…During week 9 each received labetalol 100 mg as a single dose by intravenous infusion (over 2 min) and 1 week later a further oral dose of either 100 or 200 mg was given. These studies constituted the initial single dose pharmacokinetic evaluation which was the subject of an earlier report (McNeil et al, 1979). Chronic treatment with labetalol as the sole antihypertensive agent was commenced at week 10 in a twice daily dose which was then adjusted through steps of 100, 200 and 400 mg twice daily with the aim of reducing the supine diastolic blood pressure to 90 mm Hg or less.…”
Section: Outline Of Studymentioning
confidence: 99%
“…Acute pharmacokinetic studies with the et, padrenoceptor-blocking drug labetalol in man indicate that following intravenous administration of labetalol there is a three-fold to four-fold variation in terminal elimination half-life, volume of distribution and total plasma clearance (McNeil et al, 1979). Moreover, following oral administration systemic availability of labetalol varies from 11-86%.…”
Section: Introductionmentioning
confidence: 99%
“…The elimination half-life after intravenous administration in pregnant hypertensive patients is similar to that seen with oral administration (62). The elimination half-life at steady state is significantly less than that seen in nonpregnant individuals (6-8 hours) (63), and for this reason, more frequent dosing is recommended in pregnancy (4-6 hours). Rogers et al reported a fetal/maternal serum ratio of 0.5 Ϯ 0.15 and an amniotic fluid/maternal serum ratio of 0.16 Ϯ 0.13 (61).…”
Section: Labetalolmentioning
confidence: 85%